Evaluating Inclusive Public Services In Medan City Using CoCoSo Method - Arahman, Hamjah; Hirzi, M. Fakhrul; Monica, Eka Syafrina (Universitas Budi Darma, 2025)
Ensuring the inclusiveness of public services remains a critical challenge in urban governance, particularly in decentralized regions characterized by unequal access and service quality. This study evaluates the level of public service inclusivity across sub-districts in Medan City using the Multi-Criteria Decision Making (MCDM) approach, specifically the Combined Compromise Solution (CoCoSo) method. The evaluation is based on ten inclusivity criteria covering physical and digital accessibility, service availability for vulnerable groups, service quality, transparency, community participation, and service innovation. The study employs primary data obtained through direct observations and semi-structured interviews with service users and stakeholders, as well as secondary data derived from official statistics and government documents. CoCoSo integrates the Weighted Sum Model (WSM) and Weighted Product Model (WPM) to generate stable and objective rankings of 21 sub-districts. The final CoCoSo scores range from 0.7262 to 10.7427. The results indicate that Medan Maimun and Medan Petisah achieved the highest and identical scores of 10.7427, reflecting strong performance in accessibility, service quality, and supporting infrastructure. In contrast, several sub-districts exhibit relatively low inclusivity scores, highlighting persistent disparities in service distribution and limited community participation. These findings underscore the need for targeted infrastructure development, expansion of inclusive digital services, and strengthening participatory feedback mechanisms to enhance equitable public service delivery. This study contributes a structured evaluation framework that can support evidence-based policymaking and regular monitoring of public service inclusivity at the local government level.